Stakeholders in Higher Education Accreditation: A Bibliometric Analysis - Nasrudin, Dindin; Yuningsih, Endah Kurnia; Millah, Mila Faizatul (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
The existence of stakeholders in accreditation at every level of education plays a vital role. Their opinions determine the quality of an institution. This paper aims to show research trends related to the part of stakeholders in university accreditation. The method used is a bibliometric analysis of the Scopus database using VOSviewer software. The researcher selected eight hundred ten documents from journal articles and conference proceedings in English through the selection process. The results of the co-occurrence analysis show 4 clusters of related keyword groups. Four keywords that are very influential in the research theme are quality assurance with 142 occurrences, accreditation with 83 occurrences, stakeholders with 28 occurrences, and assessment with 24 occurrences. The relationship between concepts within one cluster and between clusters is shown through network visualization. By visualizing overlays, future work related to stakeholders in higher education accreditation can be mapped, including topics on organizational culture, governance, change management, partnership, and employability. This study concludes that bibliometric analysis through VOSviewer is proven to be able to show trends and future work for stakeholder research in higher education.